2013
DOI: 10.1002/hep.26097
|View full text |Cite
|
Sign up to set email alerts
|

The Postbinding Activity of Scavenger Receptor Class B Type I Mediates Initiation of Hepatitis C Virus Infection and Viral Dissemination

Abstract: Scavenger receptor class B type I (SR-BI) is a high-density lipoprotein (HDL) receptor highly expressed in the liver and modulating HDL metabolism. Hepatitis C virus (HCV) is able to directly interact with SR-BI and requires this receptor to efficiently enter into hepatocytes to establish productive infection. A complex interplay between lipoproteins, SR-BI and HCV envelope glycoproteins has been reported to take place during this process. SR-BI has been demonstrated to act during binding and postbinding steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 39 publications
1
90
1
1
Order By: Relevance
“…To confirm SR-BI dependence for entry of HCVfrg viral subpopulations, cells were incubated prior to infection with the SR-BI antibody NK-8H5-E3 that has been shown previously to block HCVcc entry (39). In non-fractionated samples, blocking of SR-BI caused a marked decrease of infectivity of both HCVfrg and HCVcc samples in a dose-dependent manner (Fig.…”
Section: Hcvfrg Show An Uneven Dependence On Sr-bi For Entry Of Viralmentioning
confidence: 69%
“…To confirm SR-BI dependence for entry of HCVfrg viral subpopulations, cells were incubated prior to infection with the SR-BI antibody NK-8H5-E3 that has been shown previously to block HCVcc entry (39). In non-fractionated samples, blocking of SR-BI caused a marked decrease of infectivity of both HCVfrg and HCVcc samples in a dose-dependent manner (Fig.…”
Section: Hcvfrg Show An Uneven Dependence On Sr-bi For Entry Of Viralmentioning
confidence: 69%
“…Of note, their major difference-G451R, but not DHVR1, directly bind SR-BI-has been shown only with sE2, but not complete virions. 35,36 Given that SR-BI is thought to act at more than one step of the HCV-entry process, 21,22 further work will clearly be needed to define the exact effects of the different viral variants and inhibitors of the virus-SR-BI interactions. In addition, it is interesting to speculate how oxidative modification of apolipoproteins, such as ApoE and ApoC1, currently known to be associated with HCV, would affect HCV infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent work has suggested that SR-BI fulfils at least two distinct functions during viral entry: one related to initial attachment and another during post-binding. 5,21,22 Among SR-BI ligands, HDL has a modest enhancing effect on HCV entry, 23 whereas oxLDL has been found to be a strong inhibitor. 24 oxLDL is a modified form of LDL that is generated early on in the pathogenesis of atherosclerosis, when native LDL deposited in early atherosclerotic lesions (''fatty streaks'') undergoes oxidative modifications.…”
mentioning
confidence: 99%
“…A human anti-SR-BI mAb has been reported to inhibit HDL binding, to interfere with cholesterol efflux, and to decrease cell culture-derived HCV (HCVcc) entry during attachment steps without having a relevant impact on SR-BI-mediated post-binding steps (Catanese et al 2007(Catanese et al , 2010. However, SR-BI mediates the uptake of HDL-C in a two-step process including HDL binding and subsequent transfer of CE into the cell without internalization of HDL; a novel emerging hypothesis suggests that the interference with SR-BI lipid transfer function may be relevant for both initiation of HCV infection and viral dissemination independently of HDL function (Zahid et al 2013).…”
Section: Hcv Infectionmentioning
confidence: 99%
“…In this context, the post-binding activity of SR-BI is of key relevance for cell-free HCV infection as well as cell-tocell transmission and by using antibodies which do not inhibit HDL binding to SR-BI; it was observed that post-binding function of SR-BI appears to be unrelated to HDL interaction but to be directly linked to its lipid transfer function (Zahid et al 2013). So far small molecules and mAbs targeting SR-BI and interfering with HCV infection have been described (Bartosch et al 2003;Catanese et al 2007;Syder et al 2011).…”
Section: Hcv Infectionmentioning
confidence: 99%